2012
DOI: 10.1007/s12042-012-9112-y
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Banana NPR1-Like Coding Sequences Confer Similar Protection Against Pathogens in Arabidopsis

Abstract: Differences between the coding sequences of two banana homologues of the Non-expressor of Pathogenesis-Related 1 (NPR1) genes (MNPR1A and MNPR1B) were investigated as a possible cause for the differential activity of the two genes. Each of the MNPR1 coding sequences were expressed under the control of the cauliflower mosaic virus 35S promoter/terminator sequences in the transgenic Arabidopsis npr1-2 mutant. These MNPR1-expressing plants were then exposed to either the biotrophic oomycete Hyaloperonospora arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…2 a ). This is in agreement with previous results which showed a significant difference in spore numbers between the two phenotypes (data not shown) [ 32 ]. In a study of Wt and npr1 mutant plants by Cao et al [ 56 ], it was observed that infection spread event to uninfected parts of the leaf is quite rapid due to its high level of susceptibility.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…2 a ). This is in agreement with previous results which showed a significant difference in spore numbers between the two phenotypes (data not shown) [ 32 ]. In a study of Wt and npr1 mutant plants by Cao et al [ 56 ], it was observed that infection spread event to uninfected parts of the leaf is quite rapid due to its high level of susceptibility.…”
Section: Resultssupporting
confidence: 94%
“…Data analyzed in this study was derived from a study conducted at the John Innes Centre (England) in 2010 [ 32 ] and consisted of data from wild type (Wt) and npr1 mutant Arabidopsis thaliana Columbia (Col – 0) plants 48 hours post infection with Pst -DC3000 [ 34 ]. These plants were grown and inoculated under controlled greenhouse conditions (23 ° C, 10 h day/14 h dark regime and a relative humidity of 65±5 % ) in the John Innes Centre in England [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations